Bird-nest analysis: a rarely tested noninvasive survey method for monitoring mammals - Láng, Dávid L.; Bíró, Zsolt; Heltai, Miklós; Patkó, László (Archives of Biological Sciences, 2018)
Surveys of mammals can be difficult to carry out due to their elusive lifestyle and nocturnal behavior. In order to minimize the disturbance to target species, indirect or noninvasive methods are recommended. These techniques can enable the collection of samples without disturbing the animals. Active methods (e.g. hair traps) are based on artificial devices, and passive methods (e.g. scat collecting) entail the collection of samples directly from the environment. The aim of this study was to survey the mammal fauna of the Natura 2000 site of Sár-hegy in the North Hungarian Mountains based on noninvasive bird-nest analysis through the identification of hairs found in nests, based on macroscopic and microscopic features of the guard hairs. Eight out of the twelve (67%) collected nest and cavity lining materials contained good quality guard hairs. In total, 55 hair samples were found that could be analyzed, and 52 of these samples have been classified. Ten species and two twin-species were identified. The most common species was wild boar, and the most common taxa was the ruminant. There were three samples of protected species: the Eurasian beaver, the edible dormouse and the hazel dormouse-forest dormouse twin-species. The obtained findings suggest that this method can be used for monitoring the spread of species. The methodology proved to be a cheap way to collect reliable data on mammal fauna. More studies are needed to test this promising method, since gathering faunistical data can be important, especially for monitoring Natura 2000 sites. https://doi.org/10.2298/ABS170821053L Received: August 21, 2017; Revised: November 2, 2017; Accepted: November 30, 2017; Published online: December 20, 2017 How to cite this article: Láng DL, Bíró Z, Heltai M, Patkó L. Bird-nest analysis: A rarely tested noninvasive survey method for monitoring mammals. Arch Biol Sci. 2018;70(2):359-64.